2009
DOI: 10.1021/ma802270b
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Melt Grafting of N-Halamine Moieties onto Polyethylene and Their Antibacterial Activities

Abstract: Radical melt graft polymerizations of low-density polyethylene (PE) during reactive extrusion were investigated. In the absence of any reactive monomer, effects of peroxide initiator concentration and type, reaction temperature, and rotor speed of reactive extrusion on the polymer reactions were studied by monitoring mixing torque, and proper reaction conditions for the grafting reaction were proposed. Afterward, radical melt graft polymerizations of PE with several amide monomers including methacrylamide (MAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…47 Despite the fact that many publications on N-halamine 48 materials can be found, only a handful of them apply to practical 49 study leading to introduction of a product or technology on the 50 market [7,8]. 51 Poly(vinyl chloride) (PVC) belongs to the ''big five'' of polymers 52 which have large share in the total plastic production and it is still Poly(vinyl chloride) N-halamine Hydantoin Biocidal activity Thermal properties A B S T R A C T Preparation method of new biocidal plastics based on plasticized PVC has been elaborated.…”
Section: Q2mentioning
confidence: 99%
“…47 Despite the fact that many publications on N-halamine 48 materials can be found, only a handful of them apply to practical 49 study leading to introduction of a product or technology on the 50 market [7,8]. 51 Poly(vinyl chloride) (PVC) belongs to the ''big five'' of polymers 52 which have large share in the total plastic production and it is still Poly(vinyl chloride) N-halamine Hydantoin Biocidal activity Thermal properties A B S T R A C T Preparation method of new biocidal plastics based on plasticized PVC has been elaborated.…”
Section: Q2mentioning
confidence: 99%
“…Therefore, it would be beneficial to prepare environmentally-friendly superhydrophobic materials that also exhibit long-term effectiveness. Several studies have shown that N-halogenated amines can react with amines or amides to form membranes containing these compounds, although these materials show rapid declines in antimicrobial activity over time due to wear [40][41][42]. Consequently, many adhesives have been studied as means of enhancing the surface stability and wear resistance of superhydrophobic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Both low and high molecular weight N ‐halamine‐based antibacterial materials are known in the literature. In one of the approaches, either N ‐halamine containing polymers or low molecular weight N ‐halamine derivatives were added as additives to impregnate the respective polymers in order to obtain antibacterial materials 29–33. The other recent approaches involve functionalization by chemical reactions to introduce N ‐halamine structures into the desired matrix polymers 34–38.…”
Section: Introductionmentioning
confidence: 99%